Prenatal diagnosis of cystic fibrosis in combination with herpetic infection in parents with uncompensated family history - Н. П. Веропотвелян; Ю. С. Погуляй; И. В. Суховицкая; О. А. Береза; А. М. Пелых (Publishing House TRILIST, 2018)
Cystic fibrosis (CF) is a chronic genetic disorder that affects the exosecretory glands responsible for the production of mucus and sweat; as well as respiratory, digestive and reproductive systems. The article describes a brief description of this disease, the features of intrauterine manifestations and differential diagnosis with other conditions. In most cases, prenatal diagnosis of CF is offered to a family that already has children with CF. Regarding the prospective prenatal diagnosis of CF in families without CF history, as well as in couples with established status of heterozygous carrier of mutations in the CFTR gene, it is presented mainly in sporadic cases. In all other cases, prenatal diagnosis of CF is based on ultrasound detection of increased intestinal echogenicity. The hyperechogenic intestine is observed in 50-75% fetuses with CF. The incidence of intrauterine infection in fetuses with the hyperechogenic intestine is varies from 0 to 10%. The spectrum of perinatal infections is more often represented by cytomegalovirus, herpes, syphilis, toxoplasmosis, rubella and parvovirus B19. The second trimester amniotic fluid contains two main enzymes (alkaline phosphatase and gamma-glutamyltranspeptidase), whose decline of level is a reliable marker for CF. The article presents a clinical case of prenatal diagnosis of CF in combination with intrauterine infection with herpes simplex virus in 20 weeks pregnancy in a fetus with a hyperechoic intestine. When the amniotic fluid was investigated in a fetus with a normal karyotype are revealed decline of alkaline phosphatase and gamma-glutamyltranspeptidase levels, the mutation delF508 CFTR in the homozygous state and the DNA regions homologous HSV I, II types. Taking into account the unfavorable morbid prognosis, the fetus with CF was eliminated for 22 weeks pregnancy at the family's request. At autopsy were found the typical manifestations of CF in the female abortus. The molecular gene study of both parents confirmed the heterozygous carrier state. The family received recommendations on the mandatory prenatal diagnosis in subsequent pregnancies.